Autologous bone graft versus silicate-substituted calcium phosphate in the treatment of tunnel defects in 2-stage revision anterior cruciate ligament reconstruction: a prospective, randomized controlled study with a minimum follow-up of 2 years - Recum, Jan von; Gehm, Julia; Gühring, Thorsten; Vetter, Sven Y.; Linden, Philipp von der; Grützner, Paul Alfred; Schnetzke, Marc (Arthroscopy, 2020)
Purpose: To compare and evaluate knee laxity and functional outcomes between autologous bone graft and silicate-substituted calcium phosphate (Si-CaP) in the treatment of tunnel defects in 2-stage revision anterior cruciate ligament reconstruction (ACLR). Methods: This prospective, randomized controlled trial was conducted between 2012 and 2015 with a total of 40 patients who underwent 2-stage revision ACLR. The tunnels were filled with autologous iliac crest cancellous bone graft in 20 patients (control group) and with Si-CaP in the other 20 patients (intervention group). After a minimum follow-up period of 2 years, functional outcomes were assessed by KT-1000 arthrometry (side-to-side [STS] difference), the Tegner score, the Lysholm score, and the International Knee Documentation Committee score. Results: A total of 37 patients (follow-up rate, 92.5%) with an average age of 31 years were followed up for 3.4 years (range, 2.2-5.5 years). The KT-1000 measurement did not show any STS difference between the bone graft group (0.9 +/- 1.5 mm) and the Si-CaP group (0.7 +/- 2.0 mm) (P = .731). One patient in the intervention group (5%) had an STS difference greater than 5 mm. Both groups showed significant improvements in the Tegner score, Lysholm score, and International Knee Documentation Committee score from preoperative assessment to final follow-up (P <= .002), without any difference between the 2 groups (P >= .396). Complications requiring revision occurred in 4 control patients (22%) and in 2 patients in the intervention group (11%) (P = .660). No complications in relation to Si-CaP were observed. Conclusions: Equivalent knee laxity and clinical function outcomes were noted 3 years after surgery in both groups of patients. Si-CaP bone substitute is therefore a safe alternative to autologous bone graft for 2-stage ACLR.